The Influence of Sales and Purchase Financing Income on the Profitability of PT. Bank Muamalat Indonesia Tbk (Period 2006-2019) - Maulana Syarif Hidayatullah; Windi Astuti (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of murabahah financing income, istishna financing income both simultaneously and partially on profitability. The object of this research is PT. Bank Muamalat Indonesia TBK with a research period in 2006 to 2019. The method used in this study is a quantitative method with multiple linear regression techniques. Analysis techniques using multiple linear regression include the classic assumption test, the regression equation test and hypothesis testing. In data analysis using assumptions, the independent variable is murabahah financing income (X1), istishna financing income (X2) with the dependent variable is Return On Assets (Y). The results showed that simultaneously murabahah financing income and istishna financing income could explain or explain ROA of 44.1%, the rest was influenced by variables or other factors of 55.9%. While partially, murabahah financing income variable has a significant negative effect on ROA at PT. Bank Muamalat Indonesia TBK. Istishna financing income variable has a significant positive effect on ROA at PT. Bank Muamalat Indonesia TBK.